FORMATION OF THE MORAL VALUES OF THE EDUCATORS OF THE "HOUSE OF MERCY" (Academia Science Repository, 2023)
The article analyzes the methods of formation of moral values among children of orphanages by means of spiritual-educational activity, the content of forms and methods of spiritual-educational activity is revealed.